ANALISIS DAMPAK GADGET TERHADAP ASPEK PERKEMBANGAN KOGNITIF ANAK USIA DINI - Jaya, Indar; Amrizal, Amrizal (Computer Based Information System Journal, 2024)
The advent of the Fourth Industrial Revolution is considered a new hope in promoting human development. Advanced technology with automation is presented to facilitate activities and work in the daily lives of humans. One common technology found in this era is gadgets. The use of gadget technology in early childhood has become a controversial topic in recent decades, sparking debates about the impact of new technology on young children. This raises the question of whether the use of technology and the internet affects the cognitive development of young children. This research aims to analyze the impact of information technology, especially gadgets, on the level of cognitive development achievement in early childhood. The study employs a qualitative descriptive method with an interactive analysis model. The results of this research explain that the impact of information technology gadgets is both positive and negative, emphasizing the role of parents in guiding young children in the use of gadgets.